2008
DOI: 10.1118/1.2870216
|View full text |Cite
|
Sign up to set email alerts
|

Laser range scanning for image‐guided neurosurgery: Investigation of image‐to‐physical space registrations

Abstract: In this article a comprehensive set of registration methods is utilized to provide image-to-physical space registration for image-guided neurosurgery in a clinical study. Central to all methods is the use of textured point clouds as provided by laser range scanning technology. The objective is to perform a systematic comparison of registration methods that include both extracranial ͑skin marker point-based registration ͑PBR͒, and face-based surface registration͒ and intracranial methods ͑fea-ture PBR, cortical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
2
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 31 publications
0
42
2
1
Order By: Relevance
“…The points are used to provide an initial alignment which then moves on to a standard iterative closest point algorithm to complete the rigid registration process. It has been found that face-based alignment is equivalent to traditional synthetic fiducial alignment in [23]. …”
Section: Methodsmentioning
confidence: 99%
“…The points are used to provide an initial alignment which then moves on to a standard iterative closest point algorithm to complete the rigid registration process. It has been found that face-based alignment is equivalent to traditional synthetic fiducial alignment in [23]. …”
Section: Methodsmentioning
confidence: 99%
“…More importantly, because point-pair matching algorithms developed for FBR are designed to minimize the FRE, the target registration error (TRE) in the region of surgical interest, either on the cortical surface or deeper inside the brain, can be ≥5 mm. 2,24 …”
mentioning
confidence: 99%
“…28 The accuracy of extracranial SBR (based on external facial or forehead curvature) is reported to be comparable with FBR in terms of TRE. 2 Although the accuracy can be further improved by intraoperative reregistration using the cortical surface (e.g., acquired by a laser range scanner 2,24 or stereovision 6 ) or the brain volume (e.g., acquired by ultrasound 19 ), these intraoperative reregistration methods still require an initial alignment achieved by some form of patient registration, and thus they have not replaced patient registration.…”
mentioning
confidence: 99%
“…Usually, the image space and patient space were registered by these two approaches then the TRE was measured at a small number of anatomical or artificial landmarks for each method. In some studies the TRE calculated for these two registration methods was similar [5][6][7], while in others the TRE for point matching was smaller than that for surface matching [8][9][10]. According to the research on TRE distribution in point matching [11,12], the TRE varies at different points in the same registration.…”
Section: Introductionmentioning
confidence: 99%